RARE-61. BODY COMPOSITION AND NUCHAL SKINFOLD THICKNESS IN PEDIATRIC BRAIN TUMOR PATIENTS. (4th December 2020) - Peng, Junxiang; Boekhoff, Svenja; Eveslage, Maria; Bison, Brigitte; Sowithayasakul, Panjarat; Müller, Hermann L
Abstract: BACKGROUND: Obesity, cardiovascular disease (CVD), and relapse/progression have major impact on prognosis in pediatric brain tumor (BT) patients. Cranial MRI is part of routine follow-up. METHODS: In a cross-sectional study, we analyzed nuchal skinfold thickness (NST) on MRI performed for BT follow-up monitoring as a novel parameter for body composition (BC) and CVD in 177 BT patients (40 WHO grade 1–2 BT; 31 grade 3–4 BT; 106 craniopharyngioma (CP)), and 53 healthy controls (HC). Associations of NST with body mass index (BMI), waist-to-height ratio (WHtR), caliper-measured skinfold thickness (cSFT), and blood pressure (BP) were analysed in BT and HC. RESULTS: CP patients showed higher BMI, WHtR, NST and cSFT when compared with BT and HC, whereas these differences were not detectable between BT and HC. However, WHO grade 1–2 BT patients were observed with higher BMI, waist circumference and triceps cSFT when compared to WHO grade 3–4 BT patients. NST showed high correlations with BMI, WHtR, and cSFT. NST, BMI and WHtR had predictive value for CVD in terms of increased BP, and in multivariate analysis, only BMI was selected for the final model resulting in an odds ratio of 1.25 (1.14–1.379). In CP patients with hypothalamic involvement/lesion or gross-total resection, rate and degree of obesity were increased. CONCLUSIONS: As monitoring of MRI and BC play an important role in follow-up after BT, NST could serve as a novel useful parameter for assessment of BC and CVD risk in BT patients.